2009
DOI: 10.1088/0004-637x/706/1/404
|View full text |Cite
|
Sign up to set email alerts
|

The Fundamental Plane of Accretion Onto Black Holes With Dynamical Masses

Abstract: Black hole accretion and jet production are areas of intensive study in astrophysics. Recent work has found a relation between radio luminosity, X-ray luminosity, and black hole mass. With the assumption that radio and X-ray luminosity are suitable proxies for jet power and accretion power, respectively, a broad fundamental connection between accretion and jet production is implied. In an effort to refine these links and enhance their power, we have explored the above relations exclusively among black holes wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
288
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(311 citation statements)
references
References 118 publications
20
288
3
Order By: Relevance
“…It is entirely possible the data set represented in Figure 5, albeit indicative of an overall trend of radio luminosity increasing non-linearly with X-ray luminosity for sub-Eddington systems, encloses several, potentially uncorrelated phenomena that may be at the origin of its large scatter. We conclude by noticing that multiple, coordinated radio/X-ray observations of two super-massive black holes in nearby Seyfert galaxies and low-luminosity AGN, performed over periods of several months (Bell et al 2011;King et al 2011King et al , 2013, show how these systems (both akin the most radio-quiet BHBs in terms of radio-to-X-ray luminosity ratios) make almost orthogonal excursions across the fundamental plane best-fitting relation from Gültekin et al (2009), further strengthening the argument against (uncertainties in the) black hole mass or spin parameter as being entirely responsible for the large inferred intrinsic scatter.…”
mentioning
confidence: 82%
“…It is entirely possible the data set represented in Figure 5, albeit indicative of an overall trend of radio luminosity increasing non-linearly with X-ray luminosity for sub-Eddington systems, encloses several, potentially uncorrelated phenomena that may be at the origin of its large scatter. We conclude by noticing that multiple, coordinated radio/X-ray observations of two super-massive black holes in nearby Seyfert galaxies and low-luminosity AGN, performed over periods of several months (Bell et al 2011;King et al 2011King et al , 2013, show how these systems (both akin the most radio-quiet BHBs in terms of radio-to-X-ray luminosity ratios) make almost orthogonal excursions across the fundamental plane best-fitting relation from Gültekin et al (2009), further strengthening the argument against (uncertainties in the) black hole mass or spin parameter as being entirely responsible for the large inferred intrinsic scatter.…”
mentioning
confidence: 82%
“…Bagchi et al (2014) found that, when using the black hole mass to bulge mass correlation of Marconi & Hunt (2003), the black hole mass is 2.5±0.5 × 10 8 M⊙. However Bagchi et al (2014) also find that a much larger mass of 1.4×10 9 M⊙ can be found using the MBH − σ relation of Gültekin et al (2009), using the velocity dispersion averaged within the central 2.35 kpc region along the minor axis, which they find to be 351(±25) km s −1 . As the galaxy lacks a classical bulge (it has a pseudobulge), it is challenging to accurately estimate the black hole mass using scaling relations with the bulge mass, which may cause the black hole mass estimate using this method to be underestimated.…”
Section: The Energetics Of the Agnmentioning
confidence: 99%
“…During such active phases, a strong physical coupling (generally termed 'feedback') could have established a long-lasting link between hosts and SMBHs, leading to the well-known local scaling relations (e.g., Ferrarese & Merritt 2000;Gebhardt et al 2000;Gültekin et al 2009). …”
Section: Introductionmentioning
confidence: 99%